Menakar Ulang Kebijakan Pendidikan Islam: Studi Literatur atas Ketidaksesuaian Regulasi dan Praktik Lapangan - Badruzaman, Tjetjep Ismail; Maulana, Muhammad Rizal; Fauzi, Wildi Ahmad; Suherman, Usep; Sukandar, Ahmad (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
The disharmony between national education policies and the specific characteristics of Islamic education remains a fundamental issue in the development of Indonesia’s education system. This study aims to critically examine the dynamics of policy and reform in Islamic education amid the challenges of globalization, digital transformation, and decentralized governance. A qualitative-descriptive approach was employed using a library research method, analyzing policy documents, scholarly articles, and statistical data from the Ministry of Religious Affairs and the Central Statistics Agency (BPS). The findings reveal significant implementation gaps in curriculum design, funding schemes, digitalization, and teacher certification, which have negatively affected the quality and effectiveness of Islamic educational institutions. These policy misalignments have led to the marginalization of madrasahs in regional autonomy, the weakening of social legitimacy for Islamic education, and insufficient integration of Islamic values within the national education framework. The study recommends a value-based, participatory, and context-sensitive policy harmonization to strengthen the role of Islamic education in national development.ABSTRAKStudi ini bertujuan untuk mengkaji secara kritis dinamika kebijakan dan reformasi pendidikan Islam di tengah tantangan globalisasi, transformasi digital, dan desentralisasi pendidikan. Metode yang digunakan adalah studi literatur (library research) dengan pendekatan kualitatif-deskriptif, melalui penelusuran dokumen kebijakan, artikel jurnal ilmiah, serta data statistik dari Kementerian Agama dan BPS. Hasil penelitian menunjukkan adanya kesenjangan implementatif pada aspek kurikulum, pendanaan, digitalisasi, dan sertifikasi guru madrasah yang berdampak pada rendahnya kualitas dan efektivitas lembaga pendidikan Islam. Implikasi dari disharmoni ini mencakup marginalisasi madrasah dalam sistem otonomi daerah, rendahnya legitimasi sosial pendidikan Islam, dan lemahnya integrasi nilai-nilai keislaman dalam kebijakan pendidikan umum. Penelitian ini merekomendasikan pentingnya harmonisasi kebijakan yang berbasis nilai, partisipatif, dan kontekstual, guna memperkuat peran pendidikan Islam dalam pembangunan bangsa.